Interference-driven spacer acquisition is dominant over naive and primed adaptation in a native CRISPR–Cas system - Raymond H. J. Staals (Nature Portfolio, 2016)
Prokaryotic CRISPR-Cas systems provide adaptive immunity against foreign nucleic acids by acquiring short, invader-derived sequences called spacers. Here, Staals et al. analyse millions of such events in a native CRISPR-Cas system, showing that newly acquired spacers provoke additional rounds of spacer acquisition.